Melia Widiarti Peningkatan Hasil Belajar Siswa Kelas III SDN Gondek Dengan Menggunakan Direct Method pada Buku Tema 3 “Benda Di Sekitarku” - Widiarti, Melia; Soepardjo, Djodjok; Kurniawati, Wisma (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2024)
The study aimed to improve the learning outcomes on the Topic 3 “Objects Around Me” for third-grade students at SDN Gondek using a direct method. Class Action Research (PTK) was conducted over four cycles, including observation, testing, and questionnaires as data collection tools. Early observations indicated students’ difficulty in understanding the material, and this became the basis for using direct methods for improvement. Each cycle consists of planning, execution, evaluation, and reflection. Student learning outcome data were analyzed quantitatively and qualitatively, presented in graphical, tabular, and descriptive formats. The research results showed that students' learning outcomes improved significantly following the implementation of the direct method. The study concludes that it positively contributes to the improvement of students' understanding of the topic. Moreover, the study also provides the groundwork for further research on the development of learning methods aimed to improve the quality of primary education.